Pemanfaatan Sampah Organik Menjadi Media Pembelajaran Pada Sekolah Adiwiyata - Deda Widiantoro; Minsih (Elementary Teacher Education Program, Majalengka University, 2023)
Adiwiyata School is a school that has environmental sustainability programs, one of which is organic waste processing. Organic waste processing not only supports adiwiyata school programs, but can be used as a learning medium for students. Previous research has discussed many learning media, but there are still few that raise the theme of the environment in creating learning media for students. For this reason, this study aims to find out how the use of organic waste as a learning medium in adiwiyata schools. This study used a descriptive qualitative approach, with data collection using interview, observation and documentation techniques. The study was conducted on 7 female teachers and 4 male teachers, principals and supported by relevant journals. After all the data is collected, data analysis is carried out by data reduction, data presentation, and conclusions. After analyzing all data, it was found that the use of waste processing as a learning medium for students can be used as a new innovation for MIM PK Kertonatan Kartasura in implementing environment-based curriculum policies. Waste processing can be processed into new items that have use value and benefits for many people, especially it can be a learning medium that can be used by educators at MIM PK Kertonatan Kartosura. Special introduction and debriefing of waste processing skills into learning media can be done through online and offline seminars to all educators in adiwiyata school. Adiwiyata School is a school that has environmental sustainability programs, one of which is organic waste processing. Organic waste processing not only supports adiwiyata school programs, but can be used as a learning medium for students. Previous research has discussed many learning media, but there are still few that raise the theme of the environment in creating learning media for students. For this reason, this study aims to find out how the use of organic waste as a learning medium in adiwiyata schools. This study used a descriptive qualitative approach, with data collection using interview, observation and documentation techniques. The study was conducted on 7 female teachers and 4 male teachers, principals and supported by relevant journals. After all the data is collected, data analysis is carried out by data reduction, data presentation, and conclusions. After analyzing all data, it was found that the use of waste processing as a learning medium for students can be used as a new innovation for MIM PK Kertonatan Kartasura in implementing environment-based curriculum policies. Waste processing can be processed into new items that have use value and benefits for many people, especially it can be a learning medium that can be used by educators at MIM PK Kertonatan Kartosura. Special introduction and debriefing of waste processing skills into learning media can be done through online and offline seminars to all educators in adiwiyata school.